Estudio de pre-factibilidad para la producción de almidón de yuca artesanal en el recinto Lechugal cantón Ventanas provincia de Los Ríos. Guayaquil - Toaza Simisterra, Evelyn Mirielle (2017)
This research carried out the pre-feasibility studies for the extraction of cassava starch in the Cantonese Precinct of the Provinces of Los Ríos Canton; In which was set in motion what mentions the productive matrix currently promoted by the Ecuadorian government; As well as to stimulate the economy of this sector, because in the present day in this region the socio-economic level is of extreme poverty, that is to say (E); On the other hand also induces new ventures and alternative crops. The proposal of this project proposes the creation of a company dedicated to the production and extraction of cassava starch, using as the raw material the same cassava produced in this region. The methodology applied was descriptive, field, bibliographical - documentary, mixed - approach and with inductive, deductive, analysis and synthesis methods. The most relevant results are: The legal study demonstrated that there is the legal feasibility necessary in Ecuador for the establishment of this type of projects. The current juridical swarm conceives, promotes, supports and justifies the development of productive enterprises of associative type, offering the possibility of financing through private or public banks………